The Professional Rugby Experience in England and Italy - Howard Thomas; Francesco Cavatorti; Alessandro Fino (Symphonya, 2004)
The Premier Rugby League is made up of 12 professional clubs. Its mission is to promote professional rugby in England. In fulfilling this mission, it bases all activities on the League’s founding principles: a ‘large virtual family’ with values such as moral integrity. This strong sense of aggregation is a feature of the rugby community. The spirit of collaboration has also developed at the international level - formalised by an agreement with The Italian Rugby League-LIRE (Lega Italiana Rugby Eccellenza). Twinning between LIRE and Premier League means organisational and technical strengthening for each of their Clubs.